Investigating the Relationship Between Optimism and Emotional Intelligence with Academic Self-Efficacy in Orumia High School Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
BACKGROUND: The present study aims at the survey of the relationship between optimism and emotional intelligence with academic self-efficacy in high school students from Orumia in curriculum year of 2015-2016. For the same purpose, 234 individuals out of 613 students were selected based on Morgan’s table as the study sample volume, including 117 individuals from third grade and 117 individuals from the fourth grade all majoring in math, humanities and natural sciences.METHODS: The sampling method of choice has been stratified sampling. To gather the required information, Bar-on’s emotional intelligence questionnaire, Scheier’s and Carver’s inventory of optimism and Morgan-Jenkins’s self-efficacy questionnaire were applied. To analyze the data, descriptive statistic methods such as mean, median, exponent and standard deviation were used and univariate and multivariate regression tests were simultaneously implemented in the inferential statistics part. RESULTS: The results indicated that there is a significant relationship between the emotional intelligence and optimism with academic self-efficacy. Furthermore, the regression results demonstrated that emotional intelligence and optimism account for 81% and 16%, respectively, of the students’ academic self-efficacy.CONCLUSIONS: To investigate the study hypotheses, firstly, there was made use of correlation coefficient based on the data distribution normality. The results showed that there is a significant relationship between emotional intelligence and optimism with academic self-efficacy.